Komunikasi Interpersonal Dosen dan Mahasiswa Perguruan Tinggi Vokasi di Jurusan Teknik Mesin Politeknik Negeri Malang - Amrullah, Muhammad Adil; Kriyantono, Rachmat; Riani, Yuyun Agus (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This article analyzes the strategies and models of interpersonal communication of lecturers to students at vocational colleges of the Department of Mechanical Engineering, Malang State Polytechnic. The results of the study show that interpersonal communication strategies are carried out with dididic and triadic models. Meanwhile, the interpersonal communication model of lecturers and students uses an interactive model, where there is interdependence and active participation between lecturers and students. Communication anxiety, both chronic (trait apprehension) and situational (state apprehension), can be an obstacle in the interaction between lecturers and students, affecting participation, presentation quality, and students' ability to convey ideas clearly and confidently.